IMPELEMENTASI WIRELESS SEBAGAI MEDIA KOMUNIKASI PADA SOFTWARE KENDALI MANIPULATOR MOBILE MULTI LENGAN - Irwansyah, Irwansyah; Dzikrillah, Akhmad Rizal; Aditya, Muhammad Rifky; Al-Fadillah, Syafira Nadia; Makhfuz, Maulana Muhammad (ISTEK WIDURI, 2024)
Robots or manual manipulators are a type of robot whose movements are completely controlled by humans. In certain cases, errors in the robot's work area endanger humans, so manual control of the robot at close range is not recommended. Robots in certain cases need to be controlled at medium or long distances. The use of cables as a medium for transmitting control signals over medium/long distances has weaknesses in controlling mobile robots or robots whose positions dynamically move from place to place. If controlled using a cable, a manual mobile robot requires a long stretched cable so that it cannot hinder the speed of the robot's movement so it is more efficient if controlled wirelessly. Bluetooth technology can be used as a medium for wireless transmission of medium distance control signals. The aim of this research is to design wireless-based multi-arm mobile device control software. Research methods start from mechanical, electrical, user interface and robot algorithm design. The robot designed is a manual-armed robot whose movements can be controlled by a user interface device that is connected wirelessly using Bluetooth. After getting a mature design, research was carried out on making robots and interface devices. The first stage of testing was carried out to test the robot's electricity, mechanics, user interface connection with the robot, and algorithm control. If the mechanical-electrical performance is successful and the user interface is connected, and the algorithm is appropriate, then the robot is declared complete. If the electrical, mechanical and control algorithm performance does not meet expectations, then the construction of the robot will be repeated on parts of the performance that do not function as expected. By utilizing Bluetooth media on the PS2 game pad, a forklift mechanism, programming servo angles on the claws, and a holonomic wheel system, a multi-arm manipulator can be created that has 4 degrees of freedom to move objects, namely moving forward and backward, shifting right and left, lifting. - lower the object, turn left and right. The multi-arm manipulator can be controlled wirelessly using Bluetooth technology. ABSTRAKRobot atau Manipulator manual merupakan jenis robot yang pergerakannya dikendalikan oleh manusia sepenuhnya. Pada beberapa kasus tertentu, misal pada areakerja robot yang membahayakan manusia, maka pengendalian robot manual pada jarak dekat tidak disarankan. Robot pada kasus tertentu perlu dikendalikan pada jarak menengah atau jarak jauh. Penggunaan kabel sebagai media transmisi sinyal kendali jarak menengah/jauh memiliki kelemahan pada kendali robot mobile atau robot yang posisinya dinamis berpindah-pindah tempat. Jika dikendalikan menggunakan kabel maka robot mobile manual membutuhkan kabel yang terulur panjang agar tidak dapat menghambat laju gerak robot sehingga lebih efisien jika dikendalikan secara wireless. Teknologi bluetooth dapat digunakan sebagai media transmisi sinyal kendali jarak menegah secara wireless. Tujuan dari penelitian ini adalah merancang bangun software kendali perangkat mobile multi lengan berbasis wireless. Metode penelitian dimulai dari perancangan mekanik,elektrik, interface pengguna, serta algorithma robot. Robot yang dirancang adalah robot berlengan manual yang pergerakannya daoat dikendalikan oleh perangkat antarmuka pengguna yang terhubung secara wireless menggunakan bluetooth. Setelah mendapatkan perancangan yang matang, penelitian dilakukan dengan pembuatan robot dan perangkat antarmuka. Pengujian tahap pertama dilakukan untuk menguji elektrik, mekanik robot, koneksi interface pengguna dengan robot, serta algorithma kendali. Jika kinerja mekanik-elektrik berhasil serta interface pengguna terkoneksi, dan algoritma sesuai, maka robot dinyatakan selesai. Jika kinerja elektrik, mekanik, dan algorithma kendali belum sesuai ekspektasi,maka pembuatan robot akan diulangi di bagian kinerja yang belum berfungsi sesuai ekspektasi. dengan memanfaatkan media bluetooth pada game pad PS2, mekanisme forklift, pemrograman sudut servo pada capit, serta sistem roda holonomic, maka dapat dibuat manipulator multi lengan yang memiliki 4 derajat kebebasan untuk memindahkan objek yaitu bergerak maju-mundur, geser kanan-kiri, mengangkat-menurunkan objek, berbelok ke kanan-kiri. Manipulator multi lengan tersebut dapat dikendalikan secara wireless menggunakan teknologi bluetooth.